Breast screening: a randomised controlled trial in UK general practice of three interventions designed to increase uptake. Issue 1 (February 1996) - Sharp, D J; Peters, T J; Bartholomew, J; Shaw, A
Abstract : STUDY OBJECTIVES: To determine the relative effectiveness of three interventions designed to increase the uptake of breast screening. DESIGN: Randomised controlled trial of a nurse visit with health education (group A), nurse visit without health education (group B), and GP letter (group C). SETTING: The area of south east London served by the Butterfly Walk Breast Screening Unit in Camberwell. PARTICIPANTS: Women aged between 50 and 64 years who were registered with 27 GPs in the Lambeth, Southwark and Lewisham family health services authority and who had not attended for first round screening. MAIN RESULTS: Altogether 799 women were randomly allocated to the three groups. In general, delivering the nurse based interventions proved difficult. In group A, 11.4% (95% CI 7.9, 14.9%) of women subsequently attended for screening compared with 7.8% (95% CI 5.1, 11.4%) in group B and 13.1% (95% CI 7.9, 18.4%) in group C. The differences between the groups (95% CIs) were not statistically significant: A versus C, -1.7% (-8.0, +4.6%); B versus C, -5.3% (-11.3, +0.7%); A versus B, +3.6% (-1.0, +8.2%). CONCLUSIONS: A personal letter from the GP seems to be at least as effective at increasing the uptake of breast screening in non-attenders as a nurse making a home visit to discuss the issue of breast screening, and is not noticeably less effective than a visit at which a health education intervention is delivered. It is possible that the GP letter is considerably more effective than either of the two interview-based interventions. With regard to implementing strategies which will increase breast screening uptake and are cost effective, further trials of similar minimal interventions in primary care are required.